Eocene ungulate mammals from West Antarctica: Implications from their fossil record and a new species - Gelfo, Javier Nicolás; López, Guillermo M.; Santillana, Sergio N. (Antarctic Science)
Here we describe a new terrestrial mammal from the Eocene of Seymour Island (Isla Marambio) represented by a lower left third molar and assigned to a new species of Sparnotheriodontidae, an ungulate family with a broad palaeobiogeographical distribution in South America. The specimen was found in the Cucullaea I allomember of the La Meseta Formation, in a new mammalian locality (IAA 2/16). Notiolofos regueroi sp. nov. shares a brachyodont, lophoselenodont and bicrescentic molar pattern with N. arquinotiensis, recorded for a stratigraphic sequence of 17.5 Ma in Antarctica. The criteria for the species differentiation are the absence of mesial and labial cingulids, the larger paraconid, the wider talonid basin, the accentuated distal projection of the hypoconulid, the centroconid development and the smaller size. Together with the astrapotherian Antarctodon sobrali, they represent the medium to large terrestrial mammals of the early Eocene Antarctic landscape that was mostly dominated by closed forests of Nothofagus. Dental wear facets and differences in their body mass are inferred and discussed as possible evidence of niche differentiation. Additionally, the presence of land mammals with Patagonian affinities in the Eocene of Antarctica reinforces the Cretaceous-Palaeocene presence of the Weddellian Isthmus, a functional land corridor between Antarctica and South America. Fil: Gelfo, Javier Nicolás. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: López, Guillermo M. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Santillana, Sergio N. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina